A Worst-Case Robust Combination Method of Beam-Forming and Orthogonal Space–Time Block Coding - Kashiha, Mahdi; Azmi, Paeiz; Mahboobi, Behrad (Wireless personal communications, 2018)
In this paper, a new robust multi-input multi-output system is proposed in a perturbed wireless channel which is to model imperfect channel information at the source side when beam-forming and orthogonal space–time block coding is utilized. The channel perturbation is bounded by a predefined variation based on worst-case robust design. Beam-forming is used to improve the performance of the system expressed by the upper bound of pairwise error probability of symbols. In this paper firstly, the maximum value of pairwise error probability is obtained in a closed form when channel perturbation is kept below a threshold. Then the beam-forming matrix is designed to minimize the pairwise error probability subject to a predefined maximum transmitting power. This approach provides near optimal results due to using the upper bound of pairwise error probability. It shows good performance based on the symbol error rate criterion compared with other existing methods of the multiple input multiple output system.